2022
DOI: 10.1021/acsami.2c08500
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted Fabrication of Molecularly Imprinted NiAl-LDH Layer on Ni Nanorod Arrays for Glyphosate Detection

Abstract: An inorganic-framework molecularly imprinted NiAl layered double hydroxide (MI-NiAl-LDH) with specific template molecule (glyphosate pesticide, Glyp) recognition ability was prepared on Ni nanorod arrays (Ni NRAs) through electrodeposition followed by a low-temperature O2 plasma treatment. The freestanding Ni/MI-NiAl-LDH NRA electrode had highly enhanced sensitivity and selectivity. The electrocatalytic oxidation of Glyp was proposed to occur at Ni3+ centers in MI-NiAl-LDH, and the current response depended li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Figure g shows the schematic diagram of the integrated device, which includes a power supply module, microcontroller, and current measurement circuit for PEC sensing (GLY). The photograph of the electrochemical sensing device is shown in Figure h. All portable devices were placed in a camera obscura and used button batteries as mobile power. The current signal was displayed when the device was connected via a USB port.…”
Section: Resultsmentioning
confidence: 99%
“…Figure g shows the schematic diagram of the integrated device, which includes a power supply module, microcontroller, and current measurement circuit for PEC sensing (GLY). The photograph of the electrochemical sensing device is shown in Figure h. All portable devices were placed in a camera obscura and used button batteries as mobile power. The current signal was displayed when the device was connected via a USB port.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical responses of the optimized NiAl-NO 3 /Pt modified electrode were obtained by chronoamperometry at 0.49 V/ SCE with a sensitivity of 287 mA M À 1 cm 2 and a LoD of 1 μM for Glyp, the sensitivity found for Gluf was lower (178 mA M À 1 cm À 2 ). Very recently, Zhao et al [51] reported a new method to prepare NiAl-LDH electrode for glyphosate detection. A NiAl-LDH coating was prepared on Ni nanorods arrays (Ni-NRAs) by electrodeposition in the presence of Glyp in the electrolytic metal salts solution.…”
Section: Glyphosate Detectionmentioning
confidence: 99%
“…Very recently, Zhao et al. [51] reported a new method to prepare NiAl‐LDH electrode for glyphosate detection. A NiAl‐LDH coating was prepared on Ni nanorods arrays (Ni‐NRAs) by electrodeposition in the presence of Glyp in the electrolytic metal salts solution.…”
Section: Glyphosate Detectionmentioning
confidence: 99%
“…However, these methods tend to require sophisticated instrumentation, tedious pretreatments, long testing times or tedious operation. To overcome such limitations, several techniques have been proposed (Xu et al, 2018;Qin et al, 2020;Ding et al, 2021;Wu et al, 2022;Zhao et al, 2022). Among them, fluorescence methods have been receiving great attention owing to their superior analytical performances such as simplistic, rapid, and sensitive.…”
Section: Introductionmentioning
confidence: 99%